Public Perception Regarding the Use of Artificial Intelligence (AI) in the Learning Process of Elementary School (SD/MI) Students - Ummi Aisyah Siregar; Istya Nur Kharimah; Lamtama Ulan Siahaan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to describe public perception of the use of Artificial Intelligence (AI) in thelearning process of Elementary School/Islamic Elementary School (SD/MI) children, toidentify the positive and negative impacts perceived by the public, and to describe public viewsregarding the importance of parental and teacher guidance in children's use of AI. This studyemployed a quantitative descriptive approach involving 20 respondents selected randomlythrough an online questionnaire distributed via Google Form on WhatsApp social media. Theresearch instrument consisted of multiple-choice questions, a Likert scale (Strongly Disagree–Strongly Agree), and open-ended questions, which were then analyzed descriptively throughpercentage calculations and thematic grouping of responses. The results show that the majorityof respondents (65%) believe AI is already widely used by SD/MI-aged children, and 60%believe AI should begin to be introduced at grades 4–6 of elementary school. A majority ofrespondents (75%) agreed that AI helps children understand learning materials more easily;however, 95% also stated that AI use risks reducing children's independent thinking, and allrespondents (100%) agreed that SD/MI children are not yet mature enough to use AI withoutsupervision and that AI use risks lowering literacy skills if adopted early without adequatecontrol. These findings confirm that the public views AI as a potentially valuable learning aid,but its application for young children still requires active guidance from teachers and parentsso that its benefits can be optimized without neglecting the development of children's criticalthinking and literacy skills.